Instructional Delivery and Curriculum Implementation of Business Studies in Private Secondary Schools in Ilorin South Local Government Area, Kwara State - YUSUF, Habibat Abubakar; ZUBAIR, Oladimeji Mansur (International Journal of Educational Management, 2025)
This study examined the relationship between teachers’ instructional delivery and curriculum implementation in Private Secondary Schools in llorin South Local Government Area, Kwara State. A descriptive research design was adopted for the study and its population comprised 4,510 students, 4,702 secondary school teachers and 70 principals across the private secondary schools in llorin South Local Government Area. A sample of 150 students, 7 principals in private secondary schools in 1/orin South were randomly selected using Krejice and Morgan (1970) sample determination table. A checklist and questionnaire was designed and used to gather information from participants. T he items on the checklist was used to gather information on the availability of instructional resources available for the business studies programme while the questionnaire aimed at enquiring about the assessment of instructional delivery and implementation of the business studies curriculum. The instruments were given to experts to determine if its contents are suitable to illicit information from the participants. All suggestions made was incorporated in the final draft before administration. Data collected were subjected to statistical analysis with two (2) research questions raised. A checklist was used to answer research question one while research question 2 was answered using descriptive statistics of mean and standard deviation. The main hypothesis raised was tested using inferential statistics of Pearson product-moment correlation at 0.05 level of significance. The average mean for the research question 2 revealed that the instructional delivery of teacher is high but the use of instructional materials to support teaching is on the average. One of the findings of this study revealed that few of the required resources for teaching business studies were available while necessary materials required are not within the reach of the teachers, and further hinders the delivery of business studies practical. Based on this findings therefore, this study recommends that where the required teaching resources are not available, the teacher should improvise based on clear understanding of the resources recommended.